Gender Planning Dalam Hukum Islam: Corak Pemikiran dan Metode Ijtihad Syaikh Ali Jum’ah - Aisyah, Sri; Yaswirman; Fitri, Devianty (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2025)
The issue of gender planning, particularly in the form of planning to determine the sex of a fetus, is a contemporary issue arising from the rapid development of medical science and technology. From an Islamic legal perspective, this issue has given rise to differing views among Islamic scholars. This paper aims to analyze and map the characteristics of Shaykh Ali Jum'ah's Islamic legal thought and examine his methods istinbath. The law he used in establishing gender planning law. This study uses a qualitative method with a normative juridical approach, based on a literature study of the works of Sheikh Ali Jum'ah, the opinions of contemporary scholars, maqashid al-syari'ah, and fiqh al-waqi'. The results show that Sheikh Ali Jum'ah displays a moderate style of thinking (wasathiyah).Sheikh Ali Jum'ah is of the opinion that the original law of everything is permissible, so gender planning is permitted as long as it complies with sharia. This permissibility is individualized so as not to cause social imbalance. Sheikh Ali Jum'ah's ijtihad method in this matter is based on istishlahi,namely the preservation of welfare and the prevention of harm.